Expanding the Toolbox of Metal–Phenolic Networks via Enzyme‐Mediated Assembly. (4th December 2019) - Zhong, Qi‐Zhi; Richardson, Joseph J.; Li, Shiyao; Zhang, Wenjie; Ju, Yi; Li, Jianhua; Pan, Shuaijun; Chen, Jingqu; Caruso, Frank
Abstract: Functional coatings are of considerable interest because of their fundamental implications for interfacial assembly and promise for numerous applications. Universally adherent materials have recently emerged as versatile functional coatings; however, such coatings are generally limited to catechol, ( ortho ‐diphenol)‐containing molecules, as building blocks. Here, we report a facile, biofriendly enzyme‐mediated strategy for assembling a wide range of molecules (e.g., 14 representative molecules in this study) that do not natively have catechol moieties, including small molecules, peptides, and proteins, on various surfaces, while preserving the molecule's inherent function, such as catalysis (≈80 % retention of enzymatic activity for trypsin). Assembly is achieved by in situ conversion of monophenols into catechols via tyrosinase, where films form on surfaces via covalent and coordination cross‐linking. The resulting coatings are robust, functional (e.g., in protective coatings, biological imaging, and enzymatic catalysis), and versatile for diverse secondary surface‐confined reactions (e.g., biomineralization, metal ion chelation, and N ‐hydroxysuccinimide conjugation). Abstract : Das Repertoire der Metall‐Phenol‐Netzwerke wird durch eine enzymatisch vermittelte Assemblierung erweitert, bei der Monophenole in catechinhaltige Moleküle umgewandelt und durch Metallionen vernetzt werden. Diese Strategie bewahrt die Funktionalität der Monophenolvorläufer und verleiht den Netzwerken gleichzeitig Vorteile catecholhaltiger Moleküle (z. B. universelle Adhäsion).